Developing Industrial Zones in Hanoi: Current Status and Solutions - Loi, Do Van (International Journal of Global Economics and Management, 2024)
Attracting investment in industrial parks (IPs) in the city. Hanoi not only contributes to promoting the capital's overall socio-economic development, but also changes the industry structure towards prioritizing the development of new industries. The article evaluates the current status of Hanoi's industrial park development over the past time, points out the achieved results and limitations, and then proposes development solutions in the coming time.